The Effect of using Peer Partner Learning (PPL) Strategy on Iraqi EFL College Students’ Anxiety and Reading Comprehension - Haifaa Kadhim Mohummed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This study is dedicated to examine the effect of employing Peer Partner Learning (PPL) strategy on the reading comprehension and anxiety of Iraqi EFL College Students. In order to achieve the aims of the study a null hypothesis is put forward. This null hypothesis indicates that there no statistically significant differences between the experimental group (who are taught using Peer Partner Learning (PPL) strategy) and the mean score of the control group whom were taught using traditional methods. The sample of the study is limited to (44) students of EFL Iraqi college students. The result of the analysis revealed that there indeed a statistically significance difference between the mean scores of the experimental group who were instructed using Peer Partner Learning (PPL) strategy and the mean scores of the control group. Following the above results, a number of conclusions, suggestions and recommendations for upcoming research were put forward the above result, some conclusions, pedagogical recommendations and suggestions for future research have been put forward.